Evaluation of prognostic impact of pre‐treatment neutrophil to lymphocyte and lymphocyte to monocyte ratios in dogs with oral malignant melanoma treated with surgery and adjuvant CSPG4‐antigen electrovaccination: an explorative study. (15th February 2021) - Camerino, Mariateresa; Giacobino, Davide; Iussich, Selina; Ala, Ugo; Riccardo, Federica; Cavallo, Federica; Martano, Marina; Morello, Emanuela; Buracco, Paolo
Abstract: The role of systemic inflammation in cancer's progression has been widely investigated, especially in melanoma in humans. Pre‐treatment leukocyte counts and ratios play a recognized prognostic role in several types of malignancies, but no information is available regarding canine oral malignant melanoma (COMM). The purpose of this explorative retrospective study was to investigate the prognostic impact of pre‐treatment neutrophil to lymphocyte (NLR) and lymphocyte to monocyte (LMR) ratios in dogs with oral malignant melanoma that underwent surgical resection and immunotherapy with adjuvant CSPG4‐antigen electrovaccination. Thirty‐nine dogs with histologically confirmed oral melanoma and with available pre‐treatment haematological analyses, performed at maximum 60 days before the first treatment, were retrospectively enrolled. Statistical analysis was performed to explore possible correlations among NLR and LMR with age, clinical stage, tumour pigmentation, tumour size, nuclear atypia, mitotic index, Ki67, CSPG4 expression, ulceration, bone invasion and excision margins status. The impact of NLR and LMR on overall survival time (OST) was explored among various ratio cut off and across different time points with Kaplan‐Meier method. No significant relationship was identified between leukocytes ratios and histological parameters, CSPG4 expression, excision margin status, age, tumour size and clinical stage. NLR and LMR did not display a prognostic impact on the survival time of the entire population. Pre‐treatment leukocyte ratios may not represent a useful prognostic factor in dogs with oral melanoma, especially in absence of distant metastatic disease.